Carcinoma in situ and radiotherapy - Majluf, Tewfick (2015)
Actual interest of carcinoma in situ is due to relative progress in survival percentages in spite of great progress in methods of treatment in the last years, and to possible big advances in early detection by cytological methods. The attitude of the radiotherapist depends on the answer given to 2 fundamental questions: whether carcinoma in situ is, or is not a real cáncer, and if it is a cancer, what is the best treatment. It can be shown, that arguments in favor of surgical treatment are not stronger than arguments for radiation, and this is demonstrated. There is no doubt that in special cases surgery as well as radiation therapy have each their absolute indications and very particular advantages.